2007
DOI: 10.1210/en.2006-1309
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic-Pituitary-Adrenal Axis Response to Stress in Mice Lacking Functional Vasopressin V1b Receptors

Abstract: The role of arginine vasopressin (Avp) as an ACTH secretagogue is mediated by the Avp 1b receptor (Avpr1b) found on anterior pituitary corticotropes. Avp also potentiates the actions of CRH (Crh) and appears to be an important mediator of the hypothalamic-pituitary-adrenal axis response to chronic stress. To investigate the role of Avp in the hypothalamic-pituitary-adrenal axis response to stress, we measured plasma ACTH and corticosterone (CORT) levels in Avpr1b knockout (KO) mice and wild-type controls in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 78 publications
12
111
2
1
Order By: Relevance
“…It is noteworthy that in contrast to rats (Aguilera, 1998;Maet al, 1999), wild type mice shoved no habituation of ACTH responses to the repeated homotypic stress of restraint. However, V1b receptor knock out mice showed no responses to restraint stress on day 14, suggesting that V1b receptors are required for sustained responses to repeated stress (Lolait et al, 2007a). Although ACTH responses are reduced, these mice are able to display sustained corticosterone responses to the repeated stimuli.…”
Section: Does Vp Mediate Acth Responsiveness During Chronic Stress?mentioning
confidence: 98%
See 1 more Smart Citation
“…It is noteworthy that in contrast to rats (Aguilera, 1998;Maet al, 1999), wild type mice shoved no habituation of ACTH responses to the repeated homotypic stress of restraint. However, V1b receptor knock out mice showed no responses to restraint stress on day 14, suggesting that V1b receptors are required for sustained responses to repeated stress (Lolait et al, 2007a). Although ACTH responses are reduced, these mice are able to display sustained corticosterone responses to the repeated stimuli.…”
Section: Does Vp Mediate Acth Responsiveness During Chronic Stress?mentioning
confidence: 98%
“…On the other hand, studies in V1b receptor knockout mice show clear compromise of HPA axis responses to some stressors. Studies using a mouse carrying a deletion of the 3' end of the coding region of the V1b receptor show reduced ACTH responses to acute hypoglycemia, lipopolysaccharide and ethanol administration but normal basal and acute restraint-stimulated ACTH (Lolait et al, 2007a;Lolait et al, 2007b;Tanoue et al, 2004;Wersinger et al, 2002). It is noteworthy that in contrast to rats (Aguilera, 1998;Maet al, 1999), wild type mice shoved no habituation of ACTH responses to the repeated homotypic stress of restraint.…”
Section: Does Vp Mediate Acth Responsiveness During Chronic Stress?mentioning
confidence: 99%
“…CRH and AVP stimulate ACTH secretion from pituitary corticotrophs by interacting with the CRH type 1 (CRHR1) and Avpr1b or V1b receptors, respectively [62] .…”
Section: Stimulatory Activity Of Crh and Avpmentioning
confidence: 99%
“…In contrast, AVP responses mediated through the Avpr1b receptor subtype activate the phospholipase C signaling system [57,66] . The Avpr1b receptor signaling system is required for normal pituitary and adrenal responses to acute stressful stimuli and is crucial for the ACTH-release response to chronic stressors [62,66] . Moreover, previous studies have shown that AVP responses to chronic stress are stimulated by GCs, which enhance the expression of Avpr1b receptor mRNA in the hypothalamus.…”
Section: Crh/avp Receptor Signaling Systemsmentioning
confidence: 99%
“…Whereas the effects on the HPA axis are mediated by AVP/V 3 signaling in the hypothalamus (11,16,30), behavioral, and possibly autonomic, responses to stress are mediated by extrahypothalamic AVP/V 3 signaling in limbic structures, including the amygdala, hippocampus, and lateral septum (25,52). Although in acute stress responses CRF is the main activator of ACTH secretion, the AVP/V 3 system seems to play a major role during the adaptation to chronic stress conditions (1,19,26). During chronic stress, it has been shown that the hypothalamic content of AVP and V 3 receptor expression in the brain increases (2) and the peptide becomes the main modulator of the HPA axis (1,13,15,19).…”
mentioning
confidence: 99%